A new approach for forecasting OPEC petroleum consumption based on neural network train by using flower pollination algorithm - Haruna, Chiroma; Khan, Abdullah; Abubakar, Adamu; Saudi, Younes; Hamza, Mukhtar Fatihu; Shuiba, Liyana; Gital, Abdulsalam; Herawan, Tutut (Elsevier, 2016)
Petroleum is the live wire of modern technology and its operations, with economic development being positively linked to petroleum consumption. Many meta-heuristic algorithms have been proposed in literature for the optimization of Neural Network (NN) to build a forecasting model. In this paper, as an alternative to previous methods, we propose a new flower pollination algorithm with remarkable balance between consistency and exploration for NN training to build a model for the forecasting of petroleum consumption by the Organization of the Petroleum Exporting Countries (OPEC). The proposed approach is compared with established meta-heuristic algorithms. The results show that the new proposed method out performs existing algorithms by advancing OPEC petroleum consumption forecast accuracy and convergence speed. Our proposed method has the potential to be used as an important tool in forecasting OPEC petroleum consumption to be used by OPEC authorities and other global oil-related organizations.This will facilitate proper monitoring and control of OPEC petroleum consumption.